A comparative study of efficacy of resurfacing with fractional carbon dioxide laser versus derma roller in the treatment of post acne scars - Abel, Francis; Herakal, Kallappa; Shetty, Nikhita (International Journal of Research in Dermatology, 2020)
Background: Acne vulgaris is a chronic skin disease which can present as non-inflammatory lesions, inflammatory lesions, or a mixture of both, resulting in distressing and difficult to treat scars. The objective of this study is to compare the efficacy of fractional carbon dioxide (CO2) laser technique (FCLT) versus derma roller therapy (DT) with respect to post-acne scars and to study their respective side effects. Methods: A total of 200 patients of post acne scars were enrolled for this study from the outpatient Department of Dermatology, Venereology and Leprology, Navodaya Medical College Hospital and Research Centre, Raichur. The patients were randomly allocated into two groups of 100 patients each in which one group was treated with derma roller therapy and the other group was treated with fractional CO2 laser every 4 weeks over a period of 24 weeks each. Results: In the derma roller group, 89 patients completed the treatment with 11 drop out cases. The percentage reduction in the mean objective scores was found to be 37.63%. In the fractional CO2 laser group, 93 patients completed the treatment with 7 drop out cases. The percentage reduction in mean objective scores was found to be 41.22%. Conclusions: Comparing the efficacy of derma roller therapy and fractional CO2laser resurfacing method in the treatment of post acne scars, both the modalities were found to be equally efficacious.